Water-soluble rare earth elements in atmospheric deposition at Shihua Cave, Beijing, north China. (June 2019) - Peng, Xiaotao; Liu, Yuefeng; Liu, Shuhua; Cheng, Ke; Tian, Lijun; Chen, Qiong; Zhou, Houyun
Abstract: Atmospheric deposition is an important source of trace elements in speleothems. In a pilot study, atmospheric deposition was collected monthly from Shihua Cave in Beijing, North China, from November 2012 to October 2013, to tentatively investigate the annual fluxes and seasonal variations of the water-soluble rare earth elements (REEs) in atmospheric deposition. The study led to the following results: (1) the annual fluxes of all the soluble REEs were in the descending sequence Ce, 67.9 μg m −2 yr −1 ; La, 42.1 μg m −2 yr −1 ; Nd, 23.8 μg m −2 yr −1 ; Pr, 5.94 μg m −2 yr −1 ; Sm, 4.68 μg m −2 yr −1 ; Gd, 4.26 μg m −2 yr −1 ; Dy, 3.53 μg m −2 yr −1 ; Er, 2.10 μg m −2 yr −1 ; Yb, 2.00 μg m −2 yr −1 ; Eu, 0.90 μg m −2 yr −1 ; Ho, 0.77 μg m −2 yr −1 ; Tb, 0.61 μg m −2 yr −1 ; Lu, 0.32 μg m −2 yr −1 ; and Tm, 0.31 μg m −2 yr −1 . (2) The seasonal deposition fluxes of all the REEs displayed two peaks, one in the spring and the other in the autumn. Lower deposition fluxes were observed in the summer and winter. Changes in the rainfall amount and in turn soil moisture content, snow coverage of the earth surface, and atmospheric dust activity were responsible for the seasonal changes in the REE deposition fluxes. (3) Natural materials, especially wind-blown dust, were the dominant source of water-soluble REEs in atmospheric deposition. The relative contribution from anthropogenic materials, such as automobile emissions, increased significantly in the winter when the snow coverage was large and the atmospheric dust activity limited. Highlights: The deposition of water–soluble REE in Beijing displays peaks in spring and autumn. The normalized REE patterns are similar to wind-blown dust deposited in North China. Atmospheric dust activity, soil moisture and snow coverage control the flux of REE.